Heterogeneous Information Networks Node Similarity Measurement Based on Feature Sub-Graph - Biao Zhang; Chuan Li; Hongyu Xu; Yanmei Li; Ning Yang; Qian Luo (Dianxin kexue)
To solve the problem in measuring the similarity of heterogeneous information networks, a similarity measuring algorithm was proposed. It calculates the difference between the maximum common sub-graph and minimum common hyper-graph, based on feature sub-graph of the current node. The algorithm takes graph theory as its foundation, set different weight to different kinds of edges, considers nodes information as well as graph to topological information, and makes full use of the information in heterogeneous network. The result shows that the proposed algorithm has wonderful effectiveness and efficiency.